2013
DOI: 10.1186/1471-2334-13-606
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enteroviruses in children with and without hand, foot, and mouth disease in China

Abstract: BackgroundTo determine the prevalence of human enteroviruses (HEVs) among healthy children, their parents, and children with hand, foot, and mouth disease (HFMD).MethodsWe conducted a case–control study that included throat samples from 579 children with HFMD and from 254 healthy controls. Throat samples from 49 households (98 parents and 53 healthy children) were also analyzed. Phylogenetic analysis was carried out to study genetic relationships of EV71 strains.ResultsThe HEV positive rate in HFMD patients wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Data from a comprehensive and longitudinal HFMD study on the overall EV-A71 epidemiology is crucial to conclude that C2 cluster of EV-A71 found in the Philippines is only causing mild disease or even asymptomatic infection. The age range of all AFP cases is children under 15 years old, therefore, the study decided to compare the results of the study from AFP cases of the same age because a study conducted in Sweden from 2003 to 2007 has shown that the peak of EV isolation is among 18 month-old participants [25] and several other studies suggest that enteroviral infection is greater among younger children [13,26,27]. The fact that the study participants' ages (0-5 years old) do not match those of the AFP surveillance cases (0-15 years old) might be a factor for the difference in NPEV case prevalence and isolation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a comprehensive and longitudinal HFMD study on the overall EV-A71 epidemiology is crucial to conclude that C2 cluster of EV-A71 found in the Philippines is only causing mild disease or even asymptomatic infection. The age range of all AFP cases is children under 15 years old, therefore, the study decided to compare the results of the study from AFP cases of the same age because a study conducted in Sweden from 2003 to 2007 has shown that the peak of EV isolation is among 18 month-old participants [25] and several other studies suggest that enteroviral infection is greater among younger children [13,26,27]. The fact that the study participants' ages (0-5 years old) do not match those of the AFP surveillance cases (0-15 years old) might be a factor for the difference in NPEV case prevalence and isolation rate.…”
Section: Discussionmentioning
confidence: 99%
“…HFMD is a viral illness typically induced by enterovirus (EV) strains classified within species A. EV‐A71 is one of the most important infectious agents of HFMD. Other viruses known to cause HFMD include Coxsackie A (CV‐A) viruses (CV‐A2–CV‐A8, CV‐A10–CV‐A12, CV‐A16, and CV‐A20), Coxsackie B viruses (CV‐B1–CV‐B6), and enteric cytopathic human orphan viruses (E3–E6, E9, E11, E18, E25, and E30) [Ni et al, ; Zhang and Xu, ; Cui et al, ; Lin and Xue, ; Qiaoyun et al, ; Yip et al, ; Zhang et al, ,; Chen et al, ]. HFMD is most commonly associated with EV‐A71 and CV‐A16, which thus play an important role in disease outbreaks and progression [Honkanen et al, ; Hyeon et al, ; Li et al, ; Wu et al, ; Zhang et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Other viruses known to cause HFMD include Coxsackie A (CV‐A) viruses (CV‐A2–CV‐A8, CV‐A10–CV‐A12, CV‐A16, and CV‐A20), Coxsackie B viruses (CV‐B1–CV‐B6), and enteric cytopathic human orphan viruses (E3–E6, E9, E11, E18, E25, and E30) [Ni et al, ; Zhang and Xu, ; Cui et al, ; Lin and Xue, ; Qiaoyun et al, ; Yip et al, ; Zhang et al, ,; Chen et al, ]. HFMD is most commonly associated with EV‐A71 and CV‐A16, which thus play an important role in disease outbreaks and progression [Honkanen et al, ; Hyeon et al, ; Li et al, ; Wu et al, ; Zhang et al, ]. Since 2008, HFMD cases and outbreaks caused by CV‐A6 were reported in Singapore [Wu et al, ], Finland [Blomqvist et al, ], Japan [Fujimoto et al, ], Spain [Montes et al, ], and Thailand [Puenpa et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of HFMD outbreaks appears to fluctuate [3,18,19]. HFMD in tropical climate countries, such as Malaysia, Singapore and Thailand, typically showed years-round activity with no discrete epidemic periods although peaks during the rainy and winter seasons were also detected depending on season, year, and geographic regions [20,21]. At present, no specific treatment for HFMD exists.…”
Section: Introductionmentioning
confidence: 99%